Metabolomics and 16S rRNA Gene Sequencing Analyses of Changes in the Intestinal Flora and Biomarkers Induced by Gastrodia-Uncaria Treatment in a Rat Model of Chronic Migraine - Zhiqi Wen; Mingzhen He; Chunyan Peng; Yifei Rao; Junmao Li; Zhifeng Li; Lijun Du; Lijun Du; Yan Li; Maofu Zhou; Ouyang Hui; Yulin Feng; et al. (Frontiers Media S.A., 2019)
Accumulating evidence suggests that natural medicines have notable curative effects on neurological conditions, such as migraine, that are mediated by regulating the gut microbial flora. A natural medicine pair used in traditional Chinese medicine, Gastrodia elata Blume and Uncaria rhynchophylla (Miq.) Miq. ex Havil. (GU), have shown excellent effect in treating migraine, yet the role of gut microbes in the therapeutic effect of GU in chronic migraine (CMG) is unknown. Here, we performed a 16S rRNA gene sequencing and metabolomics study of the effects of GU in a nitroglycerin (NTG)-induced rat model of CMG. Our results showed that the gut microbial community structure changed significantly and was similar to that of control rats after GU administration in CMG rats. Specifically, GU increased the relative abundance of Bacteroides and Coprococcus and reduced the abundance of Prevotella_1 and Escherichia-Shigella in CMG rats. The metabolomics profiles of the plasma and ileum contents of CMG rats obtained with an ultra-performance liquid chromatography-mass spectrometer (UPLC-MS) revealed similar biomarkers in both samples, and GU treatment reduced 3-indoxyl sulfate, glutamic acid, L-tyrosine, and L-arginine levels, and increased 5-HIAA, L-tryptophan, and linoleic acid levels in plasma. Correlation analysis showed that the affected bacteria were closely related to amino acid metabolism. Most importantly, GU treatment hardly affected biomarkers in feces samples after inhibiting the activity of gut microbes. Collectively, these findings indicate that structural changes in gut flora are closely related to host metabolism and that regulating the gut microbial community structure and function may be one of the important mechanisms underlying the therapeutic effects of GU in migraine.